Adverse Pregnancy Outcomes in Overweight and Obese Women : A Cross Sectional Study (Medical Forum Monthly, 2020)
Objective: To determine maternal outcomes of pregnancy among women having increased body mass index (more than 25).Study Design: Descriptive cross-sectional studyPlace and Duration of Study: This study was conducted at the Out-patient Department of Obstetrics and Gynaecology, Nishtar Hospital Multan from 03-07-2014 to 03-01-2015.Materials and Methods: 150 pregnant women were enrolled for the research after informed consent. A proforma was filled encompassing the patients data which was analysed by SPSS -17.Results: Pre-eclampsia, Diabetes and Post partum hemorrhage was seen in 43.3 %, 21.3% and 46.7% % of the cases respectively.Conclusion: Obesity confers a high risk of gestational PPH, pre-eclampsia and gestational diabetes in pregnant women.